Peptides released by ameboid microglia regulate astroglial proliferation (The Rockefeller University Press, 1985)
Peptides that stimulate astroglial proliferation are produced in traumatized adult rat brain by 10 d after injury. These same peptides are released by ameboid microglia activated in vitro. Our findings suggest that astroglial scarring is regulated in part by the release of factors from ameboid microglia near the site of brain injury.